The Influence of Business Incubators on Entrepreneurial Economy in Makassar City, Makassar District, Bara-Baraya Timur Village - Muhammad Qadafi Zulkarnain; Amiruddin Tawe; Muhammad Rakib; Andi Annisa Sulolipu (International Journal of Economics, Commerce, and Management, 2025)
In the last few decades, entrepreneurship has become one of the main pillars of economic development, especially in developing countries like Indonesia. Makassar City, as one of the economic centers in Eastern Indonesia, has an important role in encouraging the growth of the small and medium enterprise (SME) sector. One of the efforts made by the government and various institutions is to develop a Business Incubator Program, which aims to accelerate the growth of entrepreneurs through educational support, training and guidance. In Makassar District, Bara-Baraya Timur Village, the development of local entrepreneurs is increasingly being paid attention to. Business incubators in this area offer programs to help local entrepreneurs develop business skills, increase access to capital, and open wider networks. Although business incubators have proven successful in various countries, their application in each region can certainly produce different results, depending on the characteristics of the economic and social environment. In Bara-Baraya Timur Subdistrict, there are several challenges faced by one of the local entrepreneurs who were interviewed by researchers, such as a lack of management skills, as well as increasingly fierce competition. Therefore, the researcher decided to research more deeply into "The influence of business incubators on the entrepreneurial economy in Makassar City, Bara-Baraya Timur Subdistrict".